RETRACTED: In Vitro Neuroprotective Effect Evaluation of Donepezil‐Loaded PLGA Nanoparticles‐Embedded PVA/PEG Nanofibers on SH‐SY5Y Cells and AP‐APP Plasmid Related Alzheimer Cell Line Model - Ece Guler; Humeyra Betul Yekeler; Burcu Uner; Murat Dogan; Asima Asghar; Fakhera Ikram; Yusufhan Yazir; Oguzhan Gunduz; Deepak M Kalaskar; Muhammet Emin Cam (Macromolecular Materials and Engineering, 2025)
Abstract Recently developed nanoparticles and nanofibers present new brain‐specific treatment strategies, especially for Alzheimer's disease treatment. In this study, donepezil (DO)‐loaded PLGA nanoparticles (DNP) are embedded in PVA/PEG nanofibers (DNPF) produced by pressurized gyration for sublingual administration. SEM images showed produced drug‐loaded and pure nanofibers, which have sizes between 978 and 1123 nm, demonstrated beadless morphology and homogeneous distribution. FT‐IR, XRD, and DSC results proved the produced nanoparticles and fibers to consist of the DO and other polymers. The in vitro drug release test presented that the release profile of DO is completed at the end of the 18th day. It is released by the first order kinetic model. DNPF has an ultra‐fast release profile via its disintegration within 2 sec, which proved itself to be suitable for the administration sublingually. All samples presented above ≈90% cell viability via their non‐toxic natures on SH‐SY5Y human neuroblastoma cells by using Alamar blue assay. The anti‐Alzheimer effects of DO, DNP, and DNPF are evaluated on the Aβ1−42‐induced SH‐SY5Y cells at 1, 5, and 10 µM as treatment groups. The 1 µM dosage exhibited the most significant neuroprotective effects, which showed enhanced cellular uptake and superior modulation of Alzheimer's‐related proteins, including tau and Aβ.